Small molecule TrkB agonist deoxygedunin protects nigrostriatal dopaminergic neurons from 6-OHDA and MPTP induced neurotoxicity in rodents. (December 2015) - Nie, Shuke; Xu, Yan; Chen, Guiqin; Ma, Kai; Han, Chao; Guo, Zhenli; Zhang, Zhentao; Ye, Keqiang; Cao, Xuebing
Abstract: Dopaminergic neurons loss in the substantia nigra (SN) and dopamine (DA) content loss in the striatum correlate well with disease severity in Parkinson's disease (PD). Brain-derived neurotrophic factor (BDNF) is a member of neurotrophin family and is necessary for the survival and development of DA neurons in the SN. Deficits in BDNF/TrkB receptors signaling contribute to the dysfunction of PD. Deoxygedunin, a derivative of gedunin produced from Indian neem tree, binds TrkB receptor and activates TrkB and its downstream signaling cascades in a BDNF-independent manner, and possesses neuroprotective effects in vitro and in vivo . In this study, we tested the neuroprotective effects of deoxygedunin in 6-hydroxydopamine (6-OHDA)-lesioned rat model and 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced mice model of Parkinson's disease. Rats were treated with deoxygedunin 5 mg/kg (i.p.) for one month started two weeks before 6-OHDA lesion (pre-treatment), or for two weeks right after lesion (post-treatment), with isovolumetric vehicle as control and normal. Mice were given deoxygedunin 5 mg/kg (i.p.) for 2 weeks and administrated with MPTP twice at the dose of 20 mg/kg (i.p.) on day 7. The results revealed that pretreatment with deoxygedunin improved PD models' behavioral performance and reduced dopaminergic neurons loss in SN, associated with the activation of TrkB receptors and its two major signaling cascades involving mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K). Thus, our current study indicates that deoxygedunin, as a small molecule TrkB agonist, displays prominent neuroprotective properties, providing a novel therapeutic strategy for treating Parkinson's disease. Highlights: Deoxygedunin activates TrkB receptors and signal cascades in PD animal models. Deoxygedunin mimics the effect of BDNF and possesses robust neurotrophic activities in the MPTP-treated mice. Deoxygedunin may be an innovative therapeutic agent for treating the neurodegenerative diseases.